2023
DOI: 10.3847/1538-4357/aca967
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrodynamic Evolution of Binary Black Holes Embedded within the Vertically Stratified Disks of Active Galactic Nuclei

Abstract: Stellar-mass black holes can become embedded within the disks of active galactic nuclei (AGNs). Afterwards, their interactions are mediated by their gaseous surroundings. Here, we study the evolution of stellar-mass binary black holes (BBHs) embedded within AGN disks using three-dimensional hydrodynamic simulations and analytic methods, focusing on environments where the AGN disk scale height H is ≳ the BBH sphere of influence. We model the local surroundings of the embedded BBHs using a wind tunnel formalism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…When this happens, the embedded BHs can migrate, accrete at super-Eddington rates, and potentially produce electromagnetic transients. The accretion geometry of the sBH-AGN binary depends mainly on the mass ratio of the system and the AGN disk scale height (Kaaz et al 2023). If the mass ratio is large, then the system resembles more traditional circumbinary disks, where the sBH can impact the structure of the host disk (Baruteau et al 2011;Li et al 2021).…”
Section: Disks Of Active Galactic Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…When this happens, the embedded BHs can migrate, accrete at super-Eddington rates, and potentially produce electromagnetic transients. The accretion geometry of the sBH-AGN binary depends mainly on the mass ratio of the system and the AGN disk scale height (Kaaz et al 2023). If the mass ratio is large, then the system resembles more traditional circumbinary disks, where the sBH can impact the structure of the host disk (Baruteau et al 2011;Li et al 2021).…”
Section: Disks Of Active Galactic Nucleimentioning
confidence: 99%
“…A black hole (BH) traversing through a gaseous medium is common in a wide variety of astrophysical scenarios, including common envelope evolution (MacLeod & Ramirez-Ruiz 2015;MacLeod et al 2017;Murguia-Berthier et al 2017;Everson et al 2020), wind accretion in binary systems (El Mellah & Casse 2015;El Mellah et al 2018), and the passage of stellarmass BHs through the disks of active galactic nuclei (Stone et al 2017;Kaaz et al 2023). As the BH travels through the medium, it will accrete mass and potentially produce energetic outflows that alter its environment.…”
Section: Introductionmentioning
confidence: 99%
“…The jet-cocoon evolution can also generate mechanical feedback to suppress the accretion of BH in the AGN disk (Kaaz et al 2023;Tagawa et al 2022). Assuredly, L MAD > L w may cause jet other than wind dominants the feedback.…”
Section: Jet Effect and Outflow Em Radiationmentioning
confidence: 99%
“…The CO mass capturing rate is generally hyper-Eddington, which may even exceed the mass inflow rate of the AGN disk. Previous works have artificially set upper limits for the accretion rate onto CO at the Eddington rate with various radiative efficiencies, or at the AGN disk mass inflow rate, or directly at a certain fraction of CO mass capturing rate (e.g., Tagawa et al 2020a;McKernan et al 2020b;Wang et al 2021a;Kimura et al 2021b;Kaaz et al 2023), but none has yet connected the rate to the actual accretion processes of CO. Hyper-Eddington accretion is predicted both theoretically and by numerical simulations to be accompanied by a powerful outflow of mass and energy in the form of circum-CO disk wind and collimated jet (e.g., Blandford & Begelman 1999;Ohsuga et al 2005;Begelman 2012;Gu 2012;Jiang et al 2014;Yang et al 2014;Gu 2015;Hashizume et al 2015;Saḑowski & Narayan 2016;Kitaki et al 2018;Hu et al 2022), which reduces the mass rate eventually accreted onto COs (Pan & Yang 2021b), and conversely interacts with surroundings, acting as feedback. Several recent works have investigated the feedback of CO hyper-Eddington accretion on the AGN disk environment (Wang et al 2021a;Kimura et al 2021b;Tagawa et al 2022), where Wang et al (2021a) and Kimura et al (2021b) did not concretely discuss the properties of the disk wind, while Tagawa et al (2022) mainly focused on the jetcocoon feedback from high-spin stellar-mass BHs, which may not be practical for low-spin BHs and NSs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, star-BH binaries in an AGN disk can become tightly bound due to external torques exerted by the dynamical friction of the AGN disk gas. Hydrodynamical simulations have shown that a circumbinary disk tends to shrink the orbit of the binary within an AGN disk (Li et al 2021;Kaaz et al 2021;Li & Lai 2022) and drive it to low eccentricity, either e → 0 or e → 0.45, depending on the initial value (Muñoz et al 2019;D'Orazio & Duffell 2021;Zrake et al 2021).…”
Section: Introductionmentioning
confidence: 99%